2020
DOI: 10.1186/s12913-020-05095-8
|View full text |Cite
|
Sign up to set email alerts
|

Is insurance instability associated with hypertension outcomes and does this vary by race/ethnicity?

Abstract: Background: Stable health insurance is often associated with better chronic disease care and outcomes. Racial/ ethnic health disparities in outcomes are prevalent and may be associated with insurance instability, particularly in the context of health insurance reform. Methods: We examined whether insurance instability was associated with uncontrolled blood pressure (UBP) and whether this association varied by race/ethnicity. We used a retrospective longitudinal observational cohort study of patients diagnosed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 17 publications
0
14
0
Order By: Relevance
“…Primary risk factors consisted of each participant's age, gender (male; female), educational attainment (less than high school, some college to having a college degree; higher than college), parental history of hypertension, BMI, and diagnoses of health conditions that are positively associated with hypertension, including high cholesterol, diabetes (type 1 or type 2), heart problems (e.g., heart attack, angina, rheumatic heart disease, mitral valve prolapse), and kidney problems (e.g., urine infection from kidney, kidney stone, kidney problems like nephritis or glomerulonephritis, kidney failure, dialysis, or a kidney transplant). We also included participants' insurance coverage at the Year 15 assessment, as individuals who have difficulty accessing healthcare when needed are less likely to be in control of blood pressure and other conditions co-occurring with hypertension (e.g., diabetes) [17]. Lastly, we also included three health behaviors that are associated with hypertension: [16] drinking status (current drinker; not current drinker), smoking (never smoker, former smoker, current smoker), and physical inactivity during the past year compared to people with the same gender and age (physically inactive; physically active).…”
Section: Materials and Methods Datamentioning
confidence: 99%
“…Primary risk factors consisted of each participant's age, gender (male; female), educational attainment (less than high school, some college to having a college degree; higher than college), parental history of hypertension, BMI, and diagnoses of health conditions that are positively associated with hypertension, including high cholesterol, diabetes (type 1 or type 2), heart problems (e.g., heart attack, angina, rheumatic heart disease, mitral valve prolapse), and kidney problems (e.g., urine infection from kidney, kidney stone, kidney problems like nephritis or glomerulonephritis, kidney failure, dialysis, or a kidney transplant). We also included participants' insurance coverage at the Year 15 assessment, as individuals who have difficulty accessing healthcare when needed are less likely to be in control of blood pressure and other conditions co-occurring with hypertension (e.g., diabetes) [17]. Lastly, we also included three health behaviors that are associated with hypertension: [16] drinking status (current drinker; not current drinker), smoking (never smoker, former smoker, current smoker), and physical inactivity during the past year compared to people with the same gender and age (physically inactive; physically active).…”
Section: Materials and Methods Datamentioning
confidence: 99%
“…There is evidence that post-ACA, patients receiving care in CHCs showed improvement in both hypertension and diabetes control. [14][15][16][17][18][19][20][21] Specifically, clinic level quality metrics demonstrated a greater improvement in the percent of patients with controlled diabetes and hypertension in CHCs located in expansion relative to CHCs in non-expansion states following the ACA. 16 Similarly, patients who acquired insurance post-ACA were more likely to lower their blood pressure and HbA1c than those remaining uninsured.…”
Section: Diabetes and Hypertension Controlmentioning
confidence: 99%
“…One study found duals with reduced Medicaid support or Medicaid gaps used fewer outpatient services and filled fewer prescriptions 10 . Although insurance coverage gaps and changes were demonstrated to be associated with poorer outcomes among privately insured diabetes adults 11 and nonelderly adults with hypertension, 12 no prior studies have investigated how unstable Medicaid coverage affects clinical outcomes among elderly duals. Compared with nonelderly adults, elderly duals will not become completely uninsured if they temporarily lose Medicaid coverage, albeit with higher premiums, cost sharing, and/or deductibles.…”
Section: Introductionmentioning
confidence: 99%